ANNUITIZATION BEHAVIOR: TAX INCENTIVES VS. PRODUCT DESIGN. Issue 3 (17th July 2014) - Kling, Alexander; Richter, Andreas; Ruß, Jochen
Abstract We analyze and compare the impact of tax incentives and of introducing enhanced annuities on annuitization behavior considering heterogeneity among the insured. We find that tax incentives for annuitization result in a significant increase of the portion of people who should annuitize and also an increase of the insurer's profit since less healthy individuals also annuitize, i.e. adverse selection is reduced. However, the problem that different insured receive a different value for money is even increased by tax incentives. If enhanced annuities are introduced, the percentage of insured who should annuitize further increases. Adverse selection is further reduced and the differences in value for money from annuitizing shrink.